2016
DOI: 10.14218/jcth.2016.00046
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a Promotes Lipid Droplet and Triglyceride Formation in HCV Infection by Inducing Expression of SREBP-1c and CAV1

Abstract: Aims: To examine the regulation of SREBP-1c and CAV1 by microRNA-29a (miR-29a) in cells infected with hepatitis C virus (HCV) in an attempt to control HCV-induced non-alcoholic fatty liver disease.Methods: In order to examine the manipulation of SREBP-1c and CAV1 by miR-29a, oleic acid (OA)-treated JFH-I-infected Huh-7 cells were used. OA was added 24 h post-transfection and gene expression was investigated by qRT-PCR at 48 h post treatment. The functional impact of the observed alteration in SREBP-1c and CAV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Several studies have revealed that SREBP1 could bind to the sterol regulatory elements (SREs) in the CAV1 gene promoter and subsequently negatively regulate CAV1 expression [28,29]. One recent study supported this conception in which they found SREBP1 knockdown induced by siRNA resulted in a significant increase in CAV1 mRNA level [30]. The study reporting curcumin inhibits ox-LDL-induced cholesterol accumulation in cultured rat vascular smooth muscle cells (VSMC) through increasing the caveolin-1 expression via the inhibition of nuclear translocation of SREBP1 also supported the above findings [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that SREBP1 could bind to the sterol regulatory elements (SREs) in the CAV1 gene promoter and subsequently negatively regulate CAV1 expression [28,29]. One recent study supported this conception in which they found SREBP1 knockdown induced by siRNA resulted in a significant increase in CAV1 mRNA level [30]. The study reporting curcumin inhibits ox-LDL-induced cholesterol accumulation in cultured rat vascular smooth muscle cells (VSMC) through increasing the caveolin-1 expression via the inhibition of nuclear translocation of SREBP1 also supported the above findings [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that genetic changes of Cav1 might modify the risk for breast cancer,151 and Cav1 acts both as a tumor suppressor as well as an oncogene, and plays a key role in breast cancer tumorigenesis 152. In addition to breast cancer carcinogenic process, Cav1 is also associated with lung cancer,153,154 colorectal cancer,155 gastric cancer,156,157 cervical cancer,158 hepatocellular carcinoma,159 pancreatic cancer,160 bladder cancer,161 pulmonary hypertension,162164 virus infection,165,166 cardiovascular disease,167,168 diabetes mellitus,169 nanomedicines endocytosis170 and lipodystrophy 171. Besides, it has been reported that caveo-lin-2 (Cav2) can also mediate the initiation and development of breast cancer 26…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…El-Ekiaby et al, 2012;N. M. El-Ekiaby et al, 2017;El Sobky et al, 2016;Estrabaud et al, 2015;Khanizadeh et al, 2017;Mahdy et al, 2016;Niu et al, 2016;Oksuz et al, 2015;Ono et al, 2017;Van Renne et al, 2017;G. Xu et al, 2014), influenza virus (Ingle et al, 2015;Y.…”
Section: Mir-326 Role In Cancermentioning
confidence: 99%